Evaluación de la crioconservación de espermatozoides colectados in vivo y post mortem en bovinos (Bos taurus) en el laboratorio de biotecnología de la reproducción de la carrera de medicina veterinaria de la Universidad Técnica de Cotopaxi - Carua Aguilar, María Elena (2014)
The present research was done at the Biotechnology Reproduction Laboratory of Veterinary Career at the Technical University of Cotopaxi. The main objective of this research study was to evaluate the bovine’s sperm cryopreservation using two extraction techniques: artificial vagina (live) and direct extraction of the epididymis (post mortem), to find the doable macroscopic and microscopic characteristics before freezing and after unfreezing. The cryopreservation protocol was done using the Andromed diluent: This was to prepare a one–in four solution, where 1ml. of Andromed diluent was mixed into 4 ml. of twice-distilled water at 37 ° C, then it was mixed into the half of the samples....